Yayoi Villages and Valleys - Hamada, Shinsuke (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 2007)
This article discusses analytical results on relationships between villages on plateaus and hills in the Yayoi period and valleys below them. In the past, studies of Japanese archaeology were based on a premise that wet rice paddy cultivation became common in the Yayoi Period, and it was assumed that villages on a plateau or hill had rice paddies in the valley below them. However, rice paddies in the valley tend to yield less harvest due to damage caused by cold spring water when used directly for farming. Some kind of measure was necessary, but a clear example has yet to be found. Also, even rice fields in valleys in the present day yield less crop compared to other places. They are also less stable, therefore, it was concluded that rice paddies in valleys did not yield stable harvests to sustain higher elevated villages in the Yayoi Period. For sites for which rice fields were not confirmed, wells are excavated. Based on this analysis, the relationship between a village and valley should be regarded as based on household water as the primary purpose. Examination of subsistence systems related to rice paddies in valleys was proposed as a future topic.